Effects of aging on the evolution of Apical Periodontitis lesions in rats (Research, Society and Development, 2022)
This study aimed to evaluate the effects of aging on the evolution of Apical Periodontitis (AP) lesions in rats. Elderly males (study group, n = 12) and young males (control group, n = 12) Wistar rats were used. When the study group were 24 months old and the control group were 3 months old, AP lesions were induced by creating pulp exposure of the mandibular left first molars. After 21 and 40 days, the animals were euthanized and the mandibles were removed. The left hemi- mandibles were radiographed and the AP lesions of the mesial roots of the first molars were measured using ImageJ software (National Institute of Mental Health, Bethesda, USA). The AP lesions were significantly larger in the Elderly (E) group (p = 0.0006) compared to the Control (C) group (E 21: 218.8 ± 72.96, C 21: 94.77 ± 9.44, E 40: 237.8 ± 57.20, C 40: 85.23 ± 6.63). The lesions of the animals in the elderly groups were significantly larger than the lesions in the younger animals. These findings suggest that the bone and immunological changes caused by aging can influence the progression of AP lesions.